PENGARUH PENGUMUMAN RIGHT ISSUE TERHADAP ABNORMAL RETURN DAN LIKUIDITAS : Studi Empiris Pada Bursa Efek Indonesia (BEI) - , Dwina Marsiani Soplanir, S.Si, Teologi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This purpose of this research is to the test the effect of right issue of abnormal return and liquidity. This research found 100 ample with 11 event window (from day -5 to day +5). Abnormal return was calculated by mean adjusted model. The statistical test used to test the hypothesis is to use the average difference test (paired T-test). The result showed that statistically there was significant difference between the value of abnormal return before and after the announcement right issue, showed that the Sig (P-Value) equal to 0,005 and otherwise on trading volume activity no significant difference between the value of trading volume activity before and after the announcement right issue showed that the Sig (P-Value) equal to 0,386 which this value is much greater than the value of only .05 (Sig). Then by this research show that announcement of the right issue not significantly effect trading volume activity of firms that do the right issue